Sevoflurane Improves Ventricular Conduction by Exosomes Derived from Rat Cardiac Fibroblasts After Hypothermic Global Ischemia-Reperfusion Injury - Ma Y; Cao Y; Gao H; Tong R; Yi J; Zhang Z; Chen R; Pan Z (Dove Medical Press, 2023)
Yanyan Ma,1,* Ying Cao,2,* Hong Gao,3 Rui Tong,1 Jing Yi,3 Zhongwei Zhang,1 Rui Chen,1 Zhijun Pan1 1School of Anesthesia, Guizhou Medical University, Guiyang, People's Republic of China; 2Department of Anesthesiology, The Second People's Hospital of Guiyang, Guiyang, People's Republic of China; 3Department of Anesthesiology, The Affiliated Hospital of Guizhou Medical University, Guiyang, People's Republic of China*These authors contributed equally to this workCorrespondence: Hong Gao, Department of Anesthesiology, The Affiliated Hospital of Guizhou Medical University, No. 9 Beijing Road, Guiyang, People's Republic of China, Email 2169617@qq.com; anesth@qq.comPurpose: This study investigated the effect of exosomes derived from sevoflurane-treated cardiac fibroblasts (Sev-CFs-Exo) on reperfusion arrhythmias (RA), ventricular conduction, and myocardial ischemia-reperfusion injury (MIRI).Methods: Primary cardiac fibroblasts (CFs) were isolated from the hearts of neonatal rats and identified by morphology and immunofluorescence. Exosomes were isolated from CFs at passages 2- 3 after they had been treated with 2.5% sevoflurane for an hour and cultivated for 24- 48 hours. The control group was CFs that did not receive any treatment. The hypothermic global ischemia-reperfusion injury model was established using the Langendorff perfusion technique following injection with exosomes through the caudal vein. Multi-electrode array (MEA) mapping was used to investigate the changes in RA and ventricular conduction in isolated hearts. Western blots and immunofluorescence were used to examine the relative expression and location of connexin 43 (Cx43). In addition, the MIRI was evaluated with triphenyl tetrazolium chloride and Hematoxylin-Eosin staining.Results: The primary CFs had a variety of morphologies, no spontaneous pulsation, and were vimentin-positive, which confirmed their successful isolation. Sev-CFs-Exo increased the heart rate (HR) at reperfusion for 15 minutes (T2) and 30 minutes (T3) and lowered the score and duration of RA and the time for restoration of heartbeat in reperfusion. Meanwhile, Sev-CFs-Exo increased conduction velocity (CV), decreased absolute inhomogeneity (P5-95) and inhomogeneity index (P5-95/P50) at T2 and T3, as well as promoted the recovery of HR, CV, P5-95 and P5-95/P50 after hypothermic global ischemia-reperfusion injury. Furthermore, Sev-CFs-Exo raised expression and reduced lateralization of Cx43, and improved myocardial infarct sizes and cellular necrosis. However, while cardiac fibroblast-derived exosomes (CFs-Exo) showed similar cardioprotective effects, the outcomes were not as significant.Conclusion: Sevoflurane reduces the risk of RA and improves ventricular conduction and MIRI by CFs-Exo, and this may be driven by the expression and location of Cx43.Keywords: anesthetic, extracellular vesicles, arrhythmia, electrophysiology, electrical mapping, connexin 43, Cx43